2018
DOI: 10.1093/schbul/sby136
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reducing the “Jumping to Conclusions” Bias on Treatment Decision-Making Capacity in Psychosis: A Randomized Controlled Trial With Mediation Analysis

Abstract: This is the first experimental investigation of the effect of a psychological intervention on treatment decision-making capacity in psychosis. It provides early evidence that reducing the JTC bias is associated with large and rapid improvements in capacity. Due to limited resources, assessments were administered by the researchers delivering the intervention. Results should therefore be considered preliminary and a larger, definitive trial addressing methodological limitations is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It has been suggested that JTC bias is related to the decision-making process (Turner et al, 2018), and the decision-making process based on weak evidence might be linked with a worse functioning outcome in the long term. However, the formation of delusions needs other concurrent factors, such as the necessity of closure (McKay, Langdon, & Coltheart, 2007) and overconfidence in errors (Moritz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that JTC bias is related to the decision-making process (Turner et al, 2018), and the decision-making process based on weak evidence might be linked with a worse functioning outcome in the long term. However, the formation of delusions needs other concurrent factors, such as the necessity of closure (McKay, Langdon, & Coltheart, 2007) and overconfidence in errors (Moritz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Since some therapeutic strategies have demonstrated to be useful in the treatment of JTC (Moritz et al, 2014; Roberts et al, 2014; Waller, Freeman, Jolley, Dunn, & Garety, 2011), it would be recommendable incorporating these strategies in the early treatment of CHR population. For example, recently Turner et al (2018) reported the benefits of a specific intervention derived from the meta-cognitive treatment manual developed by Moritz et al (Moritz, Woodward, & Burlon, 2007) in reducing JTC bias.…”
Section: Discussionmentioning
confidence: 99%
“…When vSZ patients are in the actual violent situations, how the moral processes guide their decision-making is incorporated into a new framework, which draws upon the concepts and findings from other moral psychology and social cognition. It is evident that patients with schizophrenia have broader reasoning biases and cognitive limitation, such as inability to fully understand goals of the task [ 49 ], difficulty in inferring what others are thinking, and having reasoning biases towards jumping to conclusions [ 50 , 51 , 52 ]. Therefore, moral reasoning represents a necessary prerequisite for information processing and, in turn, for decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The JTC is the most frequently used cognitive bias that is associated with delusional processes, and some recent studies test the hypothesis that it is a mediator of change in the treatment of psychosis (e.g., [31]). For example, in a single session intervention, JTC was reduced through cognitive therapy [31] and mediated change in overall cognitive capacity, which is assumed to be a requisite for effective nonpharmacological treatment of psychosis [32]. In the present study, JTC was targeted from a different angle, that is, on the backdrop of phenomenological assumptions on the role of disembodiment in psychosis.…”
Section: Discussionmentioning
confidence: 99%